The impact of obstructive sleep apnea-hypopnea syndrome on cognitive impairment in patients monitored at the University Clinics of Kinshasa, Democratic Republic of the Congo - Jean Paul Pholo Manzimbala; Fifi MANANA; Christian MATANDA; Gabriel LEMA; Eddy MBAMBU; Augustin NGE; Thierry MATONA; Boniface TETE; Mireille NGANGA; Richard MATANDA; Jérôme SOKOLO (Orapuh Journal)
Introduction